2005
DOI: 10.1093/icb/45.3.416
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Selection on Metabolic Rates and Related Traits in Rodents

Abstract: Artificial selection experiments are potentially powerful, yet under-utilized tool of evolutionary and physiological ecology. Here we analyze and review three important aspects of such experiments. First, we consider the effects of instrumental measurement errors and random fluctuations of body mass on the total phenotypic variation. We illustrate this with the analysis of measurements of oxygen consumption in an open-flow respirometry set-ups. We conclude that measurement errors and fluctuations of body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(131 citation statements)
references
References 48 publications
(51 reference statements)
7
122
0
2
Order By: Relevance
“…The study of Rogowitz and Chappell (Rogowitz and Chappell, 2000) reported repeatability estimates for running metabolic rate, and for one beetle species measurements separated by 2 or 4 days yielded similar repeatability values of 0.64-0.69. Comparison of studies performed by Nespolo and Franco (Nespolo and Franco, 2007) also suggest that the time between measurements did not have an impact on repeatability estimates, which appears supported by other studies in mammals (Konarzewski et al, 2005). Repeatability of metabolic rate (resting and recovery from exercise in fish) has also been shown to gradually decline over time (Norin and Malte, 2011), and a recent study suggested that this may be a general tendency (White et al, 2013).…”
Section: Repeatability Of Flight Metabolic Rate and Wingbeat Frequencysupporting
confidence: 62%
“…The study of Rogowitz and Chappell (Rogowitz and Chappell, 2000) reported repeatability estimates for running metabolic rate, and for one beetle species measurements separated by 2 or 4 days yielded similar repeatability values of 0.64-0.69. Comparison of studies performed by Nespolo and Franco (Nespolo and Franco, 2007) also suggest that the time between measurements did not have an impact on repeatability estimates, which appears supported by other studies in mammals (Konarzewski et al, 2005). Repeatability of metabolic rate (resting and recovery from exercise in fish) has also been shown to gradually decline over time (Norin and Malte, 2011), and a recent study suggested that this may be a general tendency (White et al, 2013).…”
Section: Repeatability Of Flight Metabolic Rate and Wingbeat Frequencysupporting
confidence: 62%
“…Therefore, we additionally analysed milk output according to Henderson's guidelines (Henderson, 1997;Konarzewski et al, 2005). Briefly, we expressed the magnitude of separation between the high and low lines for the milk output as the difference between the within-line mean trait values divided by the weighted phenotypic s.d.…”
Section: Statisticsmentioning
confidence: 99%
“…These authors assessed repeatability from wholeanimal metabolic rates but, as emphasized by Konarzewski et al (Konarzewski et al, 2005), whole-animal metabolic rate is intimately associated with body mass, artificially producing high and consistent repeatability of metabolism because of a reflection of body mass repeatability. The conclusion drawn by Nespolo and Franco (Nespolo and Franco, 2007) is based on 44 studies, of which only two are on fish.…”
Section: Introductionmentioning
confidence: 99%